Wood Dust Exposure Levels and Respiratory Symptoms 6 Years Apart: An Observational Intervention Study Within the Danish Furniture Industry. Issue 9 (4th June 2021) - Jacobsen, Gitte; Schaumburg, Inger; Sigsgaard, Torben; Schlünssen, Vivi
Abstract: Objectives: Occupational exposure to wood dust can cause respiratory diseases, but few studies have evaluated the impact of declining exposure on health outcome. This study aimed to investigate whether a decline in wood dust exposure between two cross sectional studies performed in 1997–1998 and 2003–2004 was related to the prevalences of respiratory symptoms among woodworkers in a well-defined geographical area. Methods: Two thousand and thirty-two woodworkers from 54 plants in study 1 and 1889 woodworkers from 52 plants in study 2 returned a questionnaire on respiratory diseases and symptoms, employment and smoking habits. Current individual wood dust exposure level was assessed from 2 study specific job exposure matrix's based on task, factory size and personal passive dust measurements (2217 in study 1 and 1355 in study 2). Results: The median (range) of inhalable dust was 1.0 mg/m 3 (0.2–9.8), 0.6 mg/m 3 (0.1–4.6) in study 1 and study 2, respectively. In study 2, the prevalence's of self-reported asthma was higher and the prevalence's of respiratory symptoms were lower compared to study 1. In adjusted logistic regression analyses using GEE methodology to account for clustering, dust exposure level could explain the differences in prevalence of coughing, chronic bronchitis and nasal symptoms between study 1 and study 2, while no effect was found for asthma. Conclusions: A 40% decline in wood dust exposure in a 6 year period may serve as an explanation for the decline in most respiratory symptoms, but do not seems to impact the prevalence of self-reported asthma.